Moving forward in the ethical consideration of invertebrates in experimentation: Beyond the Three R’s Principle - Crespi-Abril, Augusto-C. (2021)
Introduction: The Three R´s Principle (Refinement, Reduction, and Replacement), postulated more than 60 years ago, is the main ethical framework currently applied for conducting animal research. This principle has never been reviewed applying a philosophical reflection during all of these years, even though a variety of animal ethics studies have presented new insights. The Three R´s Principle was designed to be used as a policy tool to ameliorate the suffering of animals and to reduce the use of animals in research, but has failed in achieving these goals. This principle is only applied when using sentience vertebrates, and fails to consider invertebrates as their capacity to sentience is still disputed. In this way, invertebrates are reified, which has been determined to be detrimental as their suffering has been consistently denied. As a consequence, new insights are necessary to improve scientific practices. Epistemology and ethics have always been viewed as opposing approaches. ´Epistemology-based Ethics’ subordinate ethical concern to scientific facts and ‘Ethics-based Epistemology’ purports that ethical practice should guide epistemological practices. Objective: In this paper, we maintain that unifying both approaches under a broader conceptual framework may result in the view that these are not, actually, opposite approaches. We propose to progress beyond the Three R’s Principle and extend it to a position equal to the level of the ethical and epistemological approaches. We also propose to use the Precautionary Principle as it is always better to be safe than sorry, and to include two more Rs. Methods: This paper is based on the analysis of different ethical frameworks used in biology and ecology that can be implemented in invertebrates experimentation. Results: The analysis revealed that different ethical approaches are frequently used in biological research, but not all of them are implemented in experimental research that involves invertebrates. We argue that the ethical considerations used in any research field can be implemented in invertebrate research. Conclusion: We propose a Five R´s Principle: the traditional Refinement, Reduction, and Replacement, used along with Respect and Responsibility (a respectful relationship with every living being regardless of its complexity and personal commitment to conscientiously apply ethics concepts).